In-vitro effectiveness of aqueous extract of organic compost against Helminthosporium turcicum (cryptogamic disease pathogen of maize) (International Journal of Agricultural Research, Innovation and Technology, 2025)
Sustainable agriculture requires the application of biofertilizers and biopesticides in farming systems. The aim of the study was to analyze in-vitro the effect of aqueous extracts from organic compost on the development of cryptogamic disease in maize plants for yield improvement. The study was carried out in the laboratory using a pure strain of Helminthosporium turcicum previously isolated from infected maize leaves showing symptoms of the disease. Aqueous substrates of unsterilized and sterilized composts, with the concentrations 0.5, 1.0 and 2.0 mL were respectively mixed with liquid PDA at 19.5; 19 and 18 mL for a final volume of 20 ml, then aseptically poured into 90 mm diameter Petri dishes under the laminar flow hood. After solidification, 7 mm-diameter mycelial discs from young H. turcicum cultures were deposited on the agar pellets. 48 hours after incubation, mycelial growth was measured 4 times until the positive control Petri dish was invaded by mycelial filaments. The results showed that the mycelial growth of the H. turcicum strain in the presence of the sterilized aqueous compost extract was significantly reduced. Increasing the concentration significantly inhibited strain growth to the order of 95.89% at a concentration of 2 mL sterilized aqueous compost extract. Similarly, in the presence of the unsterilized aqueous compost extract, the mycelial growth of H. turcicum was also reduced. The Increasing concentration inhibited the pathogen growth by up to 76.92%, at the concentration of 2 mL. These results showed that the aqueous extract of organic compost contains compounds that could be responsible for producing suppressive substances accountable for the mechanisms inhibiting the mycelial growth of H. turcicum.Int. J. Agril. Res. Innov. Tech. 14(2): 62-73, December 2024